Reduce the equation into canonical form and find the solution
sin2x uxx+2cosx uxy - uyy=0
"sin^2x.u_{xx}+2cosx.u_{xy}-u_{yy}=0\\;\\;\\;\\;...(1)\\\\\nA=sin^2x,\\;B=2cosx,\\;C=-1"
"B^2-4AC=4(cos^2x+sin^2x)=4>0"
So, (1) hyperbolic.
"A\\lambda^2-B\\lambda+C=0\\\\\n\\Rightarrow \\lambda=cosx+1\\;\\;or, \\;cosx-1\\\\\\;\\\\\n\\therefore \\frac{dy}{dx}=cosx+1\\;or, \\;cosx-1\\\\\n\\Rightarrow y=sinx+x+c_1\\;\\;or, \\;sinx-x+c_2\\\\\nlet, \\phi(x,y)=y-sinx-x ,\\;\\;\\varphi(x,y)=y-sinx+x"
Let, "\\zeta=\\phi(x,y), \\;\\; \\eta=\\varphi (x,y)"
So,
"\\zeta =\\phi(x,y)=y-sinx-x\\\\\n\\zeta_x=-cosx-1\\\\\n\\zeta _y=1\\\\\n\\zeta_{yy}=0\\\\\n\\zeta _{xx}=sinx \\\\\nand,\\\\\n\\eta =\\varphi(x,y)=y-sin x+x\\\\\n\\eta _x=-cosx+1\\\\\n\\eta_y=1\\\\\n\\eta_{yy}=0\\\\\n\\eta_{xx}=sinx"
Now,
"u_{xx} = u_{\\zeta}(\\zeta_x^2) + 2u_{\\zeta\u03b7}\\zeta_x\u03b7_x + u_{\u03b7\u03b7}\u03b7_x^2 + u_{\\zeta}\\zeta_{xx} + u_\u03b7\u03b7_{xx}\\\\\nu_{xy} = u_{\\zeta\\zeta}\\zeta_x\\zeta_y + u_{\\zeta\u03b7}(\\zeta_x\u03b7_y + \\zeta_y\u03b7_x) + u_{\u03b7\u03b7}\u03b7_x\u03b7_y + u_\\zeta\\zeta_{xy} + u_\u03b7\u03b7_{xy}\\\\\nu_{yy} = u_{\\zeta\\zeta}\\zeta_y^2 + 2u_{\\zeta\u03b7}\\zeta_y\u03b7_y + u_{\u03b7\u03b7}\u03b7_y^2 + u_\\zeta\\zeta_{yy} + u_\u03b7\u03b7_{yy}"
Putting above values in "(1)",
we get,
"\\left(cos^4x+2cos^2x+3\\right)u_{\\zeta\\eta}\\\\\n+u_{\\zeta\\zeta}(cos^4x+2cos^3x+2cos^2x)\\\\+u_{\\eta\\eta}(cos^4x-2cos^3x+2cos^2x)=u_{\\zeta}sin^3x\\;\\;\\;...(2)\\\\"
From expressions of "\\zeta \\;and\\;\\eta,"
"x=\\frac{1}{2}(\\eta-\\zeta)\\\\"
Now from (2),
"\\left(cos^4\\frac{1}{2}(\\eta-\\zeta)+2cos^2\\frac{1}{2}(\\eta-\\zeta)+3\\right)u_{\\zeta\\eta}\\\\\n+u_{\\zeta\\zeta}(cos^4\\frac{1}{2}(\\eta-\\zeta)+2cos^3\\frac{1}{2}(\\eta-\\zeta)+2cos^2\\frac{1}{2}(\\eta-\\zeta))\\\\+u_{\\eta\\eta}(cos^4\\frac{1}{2}(\\eta-\\zeta)-2cos^3\\frac{1}{2}(\\eta-\\zeta)+2cos^2\\frac{1}{2}(\\eta-\\zeta))\\\\=u_{\\zeta}sin^3\\frac{1}{2}(\\eta-\\zeta)\\;\\;\\;...(2)\\\\"
Hence the required canonical form is :
Comments
Leave a comment